Coumarin dye with ethynyl group as p-spacer unit for dye sensitized solar cells - Torres, Erica (2016)
C1-LEN coumarin dye, containing an ethynyl conjugated bridge was tested as a new chromophore for dye-sensitized solar cells (DSSCs). Investigation on the relationship of dye structure, optical properties, electrochemical properties and performance of DSSCs is described. The C1-LEN-sensitized solar cells showed an overall conversion efficiency of 2.2% (JSC = 6.11 mA/cm2, VOC = 547 mV, FF = 0.66), which corresponds to 68% of N719-based device efficiency, fabricated under similar conditions. Electrochemical impedance spectroscopy (EIS) analysis reveals that charge recombination at the nanocrystalline TiO2/dye/redox electrolyte interface is similar for C1-LEN and N719 sensitized solar cells, i.e., charge recombination is not the factor limiting the performance of C1-LEN device.